2017
DOI: 10.1590/1981-22562017020.160095
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hospital environments and policies: seeking an age-friendly hospital

Abstract: Functional decline is one of the main problems arising from the hospitalization of elderly persons. Hospital environments and policies focused on functionality are crucial for diminishing disabilities associated with hospitalization. This observational study was performed in four internal medicine services and aimed to evaluate the hospital environment and policies as an integral step in implementing the Function-Focused Care (FFC) programme being established in Portugal. The results of the hospital environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
(8 reference statements)
1
8
1
2
Order By: Relevance
“…Most of the 34 included studies were developed within the scope of secondary care ( n = 23 articles). In this case, 13 articles focused only on a hospital department, namely, (i) Emergency Department, seven articles [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]; (ii) Surgery Department, two articles [ 34 , 35 ]; (iii) Acute Care Service, two articles [ 36 , 37 ]; (iv) Outpatient Department, one article [ 38 ]; and (v) Internal Medicine Department, one article [ 39 ]. The remaining ten articles analyze the entire hospital [ 5 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the 34 included studies were developed within the scope of secondary care ( n = 23 articles). In this case, 13 articles focused only on a hospital department, namely, (i) Emergency Department, seven articles [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]; (ii) Surgery Department, two articles [ 34 , 35 ]; (iii) Acute Care Service, two articles [ 36 , 37 ]; (iv) Outpatient Department, one article [ 38 ]; and (v) Internal Medicine Department, one article [ 39 ]. The remaining ten articles analyze the entire hospital [ 5 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acresce a necessidade de implementar, de forma mais consistente as 4 componentes de implementação do CCF para que este cuidado possa ser incorporado na prática dos enfermeiros. Importa destacar, que no processo de implementação, a componente I não demonstrou ser favorecedora da incorporação do CCF (Tavares, Grácio, & Nunes, 2017). Adicionalmente, verificou-se uma baixa adesão na componente III (estabelecimento de objetivos) e pouca clareza do papel do champion enquanto elemento motivador das equipas (componente IV).…”
Section: Discussionunclassified
“…Foram realizadas 4 visitas às unidades e entrevistados os enfermeiros(as) chefes para avaliar o ambiente (18 itens) e as políticas (15 itens), em que mais de metade dos critérios avaliados necessitam de desenvolvimento no sentido de integrar o CCF (Tavares, Grácio, & Nunes, 2017). Nas unidades experimentais, foram realizadas algumas alterações para otimizar funcionalidade/AF (ex.…”
Section: -Avaliação Do Ambiente E Das Políticasunclassified
“…FD can occur before, during, and after hospitalization due to intrinsic and extrinsic factors (Tavares, Grácio, & Nunes, 2017a). In Portugal, a study found that 76.2% of hospitalized older people were at risk for FD during and after hospitalization (Tavares et al, 2017a). Despite the high risk and significant decline rates, the authors of this study are not aware of any studies on the functional trajectory (FT) of hospitalized older people between baseline (2 weeks before hospitalization) and 3 months after discharge.…”
Section: Introductionmentioning
confidence: 91%
“…FD is one of the main consequences of hospitalization and is associated with decreased quality of life and higher mortality rates during and after hospital stay (Palese et al, 2016). FD can occur before, during, and after hospitalization due to intrinsic and extrinsic factors (Tavares, Grácio, & Nunes, 2017a). In Portugal, a study found that 76.2% of hospitalized older people were at risk for FD during and after hospitalization (Tavares et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%